2000
DOI: 10.1089/08892220050075363
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Note: Comparison of Vpu Sequences from Diverse Geographical Isolates of HIV Type 1 Identifies the Presence of Highly Variable Domains, Additional Invariant Amino Acids, and a Signature Sequence Motif Common to Subtype C Isolates

Abstract: We compared the Vpu sequences from 101 strains of HIV-1 isolated from diverse geographical regions and various subtypes in order to identify regions of high variability, and those amino acid residues that were highly conserved or invariant. In addition to the highly conserved casein kinase II (CKII) phosphorylation sites, our analysis identified additional invariant residues in the transmembrane domain and in the first and second alpha-helical domains. Our analysis revealed that all subtype C sequences had a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 15 publications
3
33
0
Order By: Relevance
“…We first amplified a fragment of 650 bp in the pol region with degenerate consensus primers designed to amplify this fragment from all known primate lentiviruses, DR1 and PolOR for the first round and Polis4/UNIPOL2 for the second round of amplification (8,10,26). PCR conditions were as reported previously (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first amplified a fragment of 650 bp in the pol region with degenerate consensus primers designed to amplify this fragment from all known primate lentiviruses, DR1 and PolOR for the first round and Polis4/UNIPOL2 for the second round of amplification (8,10,26). PCR conditions were as reported previously (10).…”
Section: Methodsmentioning
confidence: 99%
“…This was not really surprising, because even between Vpus from SIVcpz and HIV-1 group M or O, high variability has been documented. Nevertheless, the position in the genome and the length (consensus length for HIV-1 is 81 amino acids [26]) of this ORF fragment as well as the hydropathy profile displayed by its deduced protein, which is similar to Vpu (Fig. 2B), allowed us to identify this ORF as a vpu gene.…”
Section: Hiv/siv Cross-reactive Antibodies In Greater Spot-nosed Monkmentioning
confidence: 99%
“…Others have suggested that C viruses may be more stable and that their protease genes may have increased catalytic activity relative to other subtypes (72). Additional features of subtype C include a five-amino-acid insertion in the transmembrane domain of Vpu (42), a prematurely truncated second exon of rev (15,54,78), and an increase in amino acid variation at protease cleavage sites (T. de Oliveira et al, submitted for publication).…”
mentioning
confidence: 99%
“…The SIVs can also be classified into three groups based on the organization of the accessory genes in their genomes (4). All simian lentiviruses possess vif, vpr, and nef accessory genes and tat and rev regulatory genes but, until recently, only the SIVcpz and HIV-1 lineage viruses were known to have a vpu gene (4,5,27,46). SIVgsn from the greater spot-nosed monkey has now also been shown to have a vpu gene (10).…”
mentioning
confidence: 99%